2007
DOI: 10.1152/ajpendo.00366.2006
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle and heart LKB1 deficiency causes decreased voluntary running and reduced muscle mitochondrial marker enzyme expression in mice

Abstract: Thomson DM, Porter BB, Tall JH, Kim H-J, Barrow JR, Winder WW. Skeletal muscle and heart LKB1 deficiency causes decreased voluntary running and reduced muscle mitochondrial marker enzyme expression in mice. Am J Physiol Endocrinol Metab 292: E196 -E202, 2007. First published August 22, 2006; doi:10.1152/ajpendo.00366.2006.-LKB1 has been identified as a component of the major upstream kinase of AMP-activated protein kinase (AMPK) in skeletal muscle. To investigate the roles of LKB1 in skeletal muscle, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
129
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(142 citation statements)
references
References 34 publications
13
129
0
Order By: Relevance
“…The normal basal activity of CS in AMPK␣ mdKO compared with WT mice is in agreement with our previous data in these mice (29) and previous data from AMPK␣2 KD mice (1). However, a decreased basal CS activity has been found in AMPK␣2 KO (25), AMPK␣2iTG (51), AMPK␤1␤2M-KO (48), LKB1 MKO (24,54), and skmLKB1-KO mice (52). Thus, although the majority of studies suggest that altered AMPK signaling plays a role in basal CS activity, it is clearly not the sole determinant.…”
Section: Discussionmentioning
confidence: 99%
“…The normal basal activity of CS in AMPK␣ mdKO compared with WT mice is in agreement with our previous data in these mice (29) and previous data from AMPK␣2 KD mice (1). However, a decreased basal CS activity has been found in AMPK␣2 KO (25), AMPK␣2iTG (51), AMPK␤1␤2M-KO (48), LKB1 MKO (24,54), and skmLKB1-KO mice (52). Thus, although the majority of studies suggest that altered AMPK signaling plays a role in basal CS activity, it is clearly not the sole determinant.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK acts as a metabolic master switch regulating several intracellular systems including the cellular uptake of glucose, the β-oxidation of fatty acids, and the biogenesis of glucose transporter 4 and mitochondria [44,45]. The energy-sensing capability of AMPK can be attributed to its ability to detect and react to fluctuations in the AMP:ATP ratio that take place during rest and exercise [45,46]. AMPK signaling pathways are activated by adipokines, including adiponectin and leptin secreted from adipose tissues, which play several distinct but important physiological and pathological roles in the body [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…14 In situ electrical stimulation-induced AMPK phosphorylation/activity is abolished to a large extent in the absence of LKB1, and thus, at least under these conditions, LKB1 seems to be the principal AMPK regulator in mouse skeletal muscle. 15,16 In skeletal muscle, AMPK is activated by acute exercise in both rodents and humans in an exercise intensity-dependent manner. Exercise at 60-75% of VO 2peak appears to be necessary for AMPK activation in humans (for references see Wojtaszewski et al 17 ) and at these intensities complexes containing a2-AMPK are regulated to a greater extent than complexes containing a1-AMPK.…”
Section: Expression Of Ampk In Skeletal Musclementioning
confidence: 99%
“…45 Yet in support of a role for AMPK signalling in expression of mitochondrial proteins, we have found that basal expression of a number of mitochondrial proteins was significantly reduced in nontrained a2-AMPK KO mice 45 and recently similar observations were reported in the LKB1 KO mouse. 15 Thus, it is likely that the disturbed energy balance observed during acute exercise in the a2-AMPK KO (and likely also in the LKB1 KO mouse) partly results from decreased ability to generate ATP.…”
Section: Involvement Of Ampk In Mitochondrial Biogenesis In Skeletal mentioning
confidence: 99%